1993
DOI: 10.1590/s0037-86821993000400003
|View full text |Cite
|
Sign up to set email alerts
|

Evolução da resistencia in vitro do Plasmodium falciparum a antimaláricos em área de prospecção de ouro no Estado do Amapá, entre 1983 e 1990

Abstract: A resistência do Plasmodium falciparum às drogas antimaláricas representa um dos maiores obstáculos para o êxito de combate e controle da malária em muitas áreas onde a doença ocorre.N oB rasilJáem 1910, registrava-se o primeiro insucesso no tratamento da malária como quinino13.Para a cloroquina o primeiro registro de resistência na América do Sul ocorreu no final dos anos 50, na Colômbia28 e no Brasil18 21. Atualmente a resistência às drogas é um fenômeno muito comum em diversas áreas da região amazônica bras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Two previous surveillance studies of drug-resistant malaria in the Amazon region demonstrated a high level of chloroquine resistance. 5,30 Thus, in this case the in vitro data correlates with the in vivo clinical resistance. An attempt to treat malaria in the Amazon region using a high-dose regimen of chloroquine may have delayed the development of clinical resistance, but it did not prevent it.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Two previous surveillance studies of drug-resistant malaria in the Amazon region demonstrated a high level of chloroquine resistance. 5,30 Thus, in this case the in vitro data correlates with the in vivo clinical resistance. An attempt to treat malaria in the Amazon region using a high-dose regimen of chloroquine may have delayed the development of clinical resistance, but it did not prevent it.…”
Section: Resultsmentioning
confidence: 80%
“…Several factors are associated with the emergence of drug resistance, but certainly a major contributing factor is the drug pressure in the region. 5 Today, in many malaria-endemic areas of Brazil clinical failures of chloroquine are reaching 100% and the drug is no longer recommended for treatment of uncomplicated P. falciparum malaria (Pang L, Walter Reed Army Institute of Research [WRAIR], unpublished data). With the advent of chloroquine resistance, other antimalarials were introduced.…”
mentioning
confidence: 99%
“…Similar results have been showed by many authors. 13,[15][16][17][18][19] Our results indicate a direct correlation between the geographical dispersion and the different resistance rates. Similar observations have been pointed out in Brazilian Amazonia.…”
Section: Resultsmentioning
confidence: 87%
“…As is known, self-medication and subcurative doses favor the selection of resistant parasite populations, which are frequent in areas of high malarial transmission. [8][9][10][11][12][13][14] Another factor that may influence the development of high resistance of P. falciparum to chloroquine (although no studies have been performed) could be the uncontrolled population migration movements within and into and out of the municipality of Domingo Sifontes and surrounding areas, as proposed above. Similar results have been showed by many authors.…”
Section: Resultsmentioning
confidence: 99%